PERAN PENYULUH PERIKANAN TERHADAP USAHA KELOMPOK PENGOLAHAN DAN PEMASARAN (POKLAHSAR) “PARI EMAS” DI KELURAHAN MANGGAR BARU KECAMATAN BALIKPAPAN TIMUR - Agus Purnomo; Muhammad Syafril; Nurul Ovia Oktawati (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
This study aims to determine the level of the role of extension agents in increasing business productivity of POKLAHSAR "Pari Emas", and to find out the business feasibility of POKLAHSAR "Pari Emas" in Manggar Baru Village, East Balikpapan District. The study was conducted based on descriptive data collection methods to obtain a factual and concrete picture of the Role of Fisheries Extension Workers in the POKLAHSAR Processing and Marketing Group Business "Pari Emas" in Manggar Baru Village, East Balikpapan District and the data was then processed and analyzed quantitatively. The results showed that the role of extension agents in increasing business productivity from POKLAHSAR "Pari Emas" in Manggar Baru Village, East Balikpapan Subdistrict was in the high category with an average score of 8.1 and Business from POKLAHSAR "Pari Emas" was feasible to develop RCR value of 1.49.